The Scientific Papers of Tjalling C. Koopmans: A Review Article* - Malinvaud, Edmond (Journal of Economic Literature, 2016)
THIRTY YEARS AGO, when Koopmans began to be well known as an economist, he seemed to be a foreigner in a field where his approach to problems was often so different from the prevailing ones. Today a large group of young economists follows his path to scientific discovery. In this respect the book under review is particularly interesting. Not only does it serve as an easy access to articles that appeared in a large number of journals, but it also gives to the careful reader an opportunity to understand the true personality of Tjalling Koopmans, the scientist, and, beyond him, the methodology of modern economics.